Germany : Staff Report for the 2012 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
This 2012 Article IV Consultation reports that the German economy's performance has been remarkable despite facing considerable headwinds. Several conditions are now in place in Germany for a domestic demand-led recovery. Employment creation has been robust and unemployment at 5.3 percent is at a postreunification low. Executive Directors have commended Germany's strong macroeconomic management, which has resulted in a favorable economic performance despite the uncertain external environment. Directors have underscored Germany's pivotal role in reducing euro area and global imbalances.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet